Monitoring of Raw and Treated Water Quality Based on Nitrate Parameter at Ngagel Water Treatment Plant Using Spectrophotometry Method - Sudrajat, Oka Akbar; Wardhani, Primasari Cahya; Timur, Fajar; Pravitasari, Rizky; Rizkiarna, Reffany Choiru; Perwitasari, Devina Rayzy (Faraday: Journal of Fundamental Physics, Research, and Applied Science, 2025)
This research focuses on monitoring the water quality at the Ngagel Water Treatment Plant in Surabaya by analyzing the nitrate (NO₃⁻) content in both raw and treated water. Nitrate is a key indicator of water pollution, often originating from agricultural runoff, sewage, and industrial discharge. Samples were collected monthly from January to March 2024 at two locations: the raw water intake from the Surabaya River and the treated water output ready for distribution. Laboratory testing using spectrophotometric methods showed that nitrate levels in raw water ranged between 2.44 mg/L and 3.50 mg/L, while treated water showed a slightly lower range between 2.00 mg/L and 3.00 mg/L. These results indicate a consistent reduction in nitrate concentrations after treatment, demonstrating the efficiency of the Ngagel Water Treatment Plant’s processes. Importantly, all measured values were significantly below the maximum allowable limit of 50 mg/L, as stated in the Indonesian Ministry of Health Regulation No. 492/MENKES/PER/IV/2010. This confirms that the treated water is safe for human consumption with regard to nitrate levels. The study highlights the importance of continuous water quality monitoring to ensure public health protection and to maintain the effectiveness of water treatment facilities over time.